Marketing educativo y la captación de clientes en la I.E.P. “El Honguito” de Casma, Año 2021 - Acuña Perez, Janeth Yovana (2021)
The main objective of this study was to determine the relationship between educational marketing and customer acquisition in the I.E.P. El Honguito, in the city of Casma in 2021. Regarding the methodology, the study was applied and quantitative, in addition to presenting a cross-sectional, correlational and nonexperimental approach. The population consisted of 60 parents of the I.E.P. El Honguito and that due to being a small population (60), it was used in its entirety as a sample (census). For the data collection, 2 questionnaires were required, one for educational marketing and the other for customer acquisition. Regarding the statistical test, the Spearman statistical test was used. With all this, it was concluded that there is a directly proportional relationship between educational marketing and customer acquisition in said institution, with a Spearman coefficient equal to 0.658 and a significance of 0.000, which is why it is suggested to the general administration of the IEP El Honguito, invest in an educational marketing plan to improve customer engagement.